2015
DOI: 10.1039/c4ra11135d
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of MoS2/SrZrO3 heterostructures and their photocatalytic H2 evolution under UV irradiation

Abstract: A novel heterojunction of a MoS2/SrZrO3 photocatalyst was successfully synthesized via a simple hydrothermal process and applied to photocatalytic H2 evolution under UV light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
0
24
2
Order By: Relevance
“…Recently, Tian et al. synthesized a novel heterojunction of a MoS 2 /SrZrO 3 photocatalyst (via a simple hydrothermal process) and applied it for photocatalytic H 2 evolution under UV light irradiation. The rate of H 2 evolution for pure SrZrO 3 photocatalyst (with Na 2 S/Na 2 SO 3 as a sacrificial agent) was 9.75 mmol h −1 g −1 whereas the rate was increased 2.7 times to reach 26.55 mmol h −1 g −1 by introducing 0.05 wt.…”
Section: Mos2‐based Composites As Photocatalysts For the Splitting Ofmentioning
confidence: 99%
“…Recently, Tian et al. synthesized a novel heterojunction of a MoS 2 /SrZrO 3 photocatalyst (via a simple hydrothermal process) and applied it for photocatalytic H 2 evolution under UV light irradiation. The rate of H 2 evolution for pure SrZrO 3 photocatalyst (with Na 2 S/Na 2 SO 3 as a sacrificial agent) was 9.75 mmol h −1 g −1 whereas the rate was increased 2.7 times to reach 26.55 mmol h −1 g −1 by introducing 0.05 wt.…”
Section: Mos2‐based Composites As Photocatalysts For the Splitting Ofmentioning
confidence: 99%
“…Among them, SrZrO 3 is an n-type perovskite semiconductor with a wide band gap, and it has been used as photocatalyst, proton-conductor material, high voltage and high reliability capacitor [24,25]. Recently, Tian et al [26] synthesized SrZrO 3 with a small amount of MoS 2 loaded on the surface of SrZrO 3 and applied the material as the photocatalyst for H 2 evolution. The result indicated that SrZrO 3 exhibited great potential in photocatalytic field.…”
mentioning
confidence: 99%
“…The Ru 0 /Ru 4+ ratio of 62.2:37.8 by XPS curve fitting was observed, demonstrating that some RuO 2 species still exist on the catalyst after H 2 reduction. Notably, the peak of C 1s at 284.7 eV should be a result of C–C carbon from the residue of polyvinylpyrrolidone. , …”
Section: Resultsmentioning
confidence: 99%